Personnel Interviewing Via Videoconferencing - Don Bower; Joe Courson; Janet Frazier (Journal of Applied Communications, 1994)
Videoconferencing has many uses in education and management, and the University of Georgia Cooperative Extension Service tried a new application of the technology.